2011
DOI: 10.1038/eye.2011.270
|View full text |Cite
|
Sign up to set email alerts
|

Corneal nerve alterations in acute Acanthamoeba and fungal keratitis: an in vivo confocal microscopy study

Abstract: Purpose To study sub-basal corneal nerve alterations in patients with acute Acanthamoeba keratitis (AK) and fungal keratitis (FK), using laser in vivo confocal microscopy (IVCM). Methods A retrospective analysis of IVCM (Heidelberg Retina Tomograph 3/Rostock Cornea Module) images of 10 AK corneas and 4 FK corneas was performed, and the results compared with those of 10 normal and 12 acute herpetic keratitis (HK) corneas. Sub-basal corneal nerves were analyzed with respect to total number of nerves, main nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 14 publications
0
48
0
Order By: Relevance
“…The degree of sensitivity loss correlates with the severity of clinical disease. The loss of sensitivity in corneas of patients with HSK is thought to be irreversible (12) and associated with loss of nerve fibers extending from the corneal stroma into the epithelium (13,14). Nerve damage in corneas with HSK is assumed to be related to HSV-1 neurotropism, but it is unclear if damage is directly mediated by HSV-1 infection or is immunologically mediated.…”
mentioning
confidence: 99%
“…The degree of sensitivity loss correlates with the severity of clinical disease. The loss of sensitivity in corneas of patients with HSK is thought to be irreversible (12) and associated with loss of nerve fibers extending from the corneal stroma into the epithelium (13,14). Nerve damage in corneas with HSK is assumed to be related to HSV-1 neurotropism, but it is unclear if damage is directly mediated by HSV-1 infection or is immunologically mediated.…”
mentioning
confidence: 99%
“…It has also been found that corneal sensation may be decreased after fungal infection, supported by in vivo confocal microscopy showing decreased corneal nerve length as well as nerve counts [38].…”
Section: Clinical Outcomesmentioning
confidence: 80%
“…[15][16][17][18] In this study, high resolution laser IVCM was used to diagnose different kinds of concealed corneal foreign bodies. Results showed that glass corneal foreign bodies were more highly reflective than other foreign bodies and had a knife-edged appearance.…”
Section: Discussionmentioning
confidence: 99%